The Role of Pathogen Dynamics and Immune Gene Expression in the Survival of Feral Honey Bees - Hinshaw, Chauncy; Evans, Kathleen C.; Rosa, Cristina; López-Uribe, Margarita M. (Frontiers in Ecology and Evolution, 2021)
Studies of the ecoimmunology of feral organisms can provide valuable insight into how host-pathogen dynamics change as organisms transition from human-managed conditions back into the wild. Honey bees (Apis mellifera Linnaeus) offer an ideal system to investigate these questions as colonies of these social insects often escape management and establish in the wild. While managed honey bee colonies have low probability of survival in the absence of disease treatments, feral colonies commonly survive in the wild, where pathogen pressures are expected to be higher due to the absence of disease treatments. Here, we investigate the role of pathogen infections [Deformed wing virus (DWV), Black queen cell virus (BQCV), and Nosema ceranae] and immune gene expression (defensin-1, hymenoptaecin, pgrp-lc, pgrp-s2, argonaute-2, vago) in the survival of feral and managed honey bee colonies. We surveyed a total of 25 pairs of feral and managed colonies over a two-year period (2017-2018), recorded overwintering survival, and measured pathogen levels and immune gene expression using quantitative Polymerase Chain Reaction (qPCR). Our results show that feral colonies had higher levels of DWV but it was variable over time compared to managed colonies. Higher pathogen levels were associated with increased immune gene expression, with feral colonies showing higher expression of five out of the six examined immune genes for at least one sampling period. Further analysis revealed that differential expression of the genes hymenoptaecin and vago increased the odds of overwintering survival in managed and feral colonies. Our results suggest that feral colonies express immune genes at higher levels in response to high pathogen burdens, providing evidence for the role of feralization in altering pathogen landscapes and host immune responses.